THE ROLE OF THE LANDSCAPE FACTOR IN URBAN TRADITIONS OF THE LOCAL POPULATION (Scientific journal of the Fergana State University, 2023)
The article discusses the ability of the local population of Ferghana Valley to use the possibilities of the landscape factor when creating settlements. The issues of adaptation to natural conditions, the use of water resources, which are considered its task, are covered in the formation of the cities of the valley.